Clean/Unclean, Pure/Impure, Holy/Profane - Lawrence, Jonathan David (The Oxford handbook of ritual and worship in the Hebrew Bible, 2020)
This chapter explores the biblical ideas of purity and the related concepts of cleanness and holiness. It discusses some of the terminology used for these concepts in the Bible and related literature and how these terms are used in different texts and various periods. It examines the relationship between purity and holiness, particularly in terms of the Temple in Jerusalem, and discusses some of the possible reasons that certain materials were designated as unclean or impure. It also outlines the development of purification practices, particularly in terms of miqva’ot, Jewish ritual baths which were introduced in the Second Temple period.